The Correlation Between Resilience And Career Readiness of SMA Negeri 1 Malang Students - Annisa’ Taqiyyatul ‘Azizah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Adolescence is a crucial developmental stage because adolescents experience various important changes. The most important cognitive change in adolescence is an increase in executive function, which involves high-level cognitive activities such as reasoning, decision making, critical thinking skills, and increasing one's cognitive abilities. Adolescents in this stage are faced with new experiences to find identity, one of which is to explore interests and talents as well as career paths to be pursued. Currently, many changes are occurring, one of which is the transition from industry 4.0 to industry 5.0. This situation requires each individual to adapt and face freedom in the career transition period. The purpose of this study was to identify the effects of resilience on the career readiness of students at SMA Negeri 1 Malang. The technique used in this study is correlational descriptive quantitative research with a random sampling system. The results of the Pearson correlation show that there is a significant relationship between resilience and career readiness as evidenced by the results of the linearity test value of 0.876 (p > 0.05).